Using Video Game Telemetry Data to Research Motor Chunking, Action Latencies, and Complex Cognitive‐Motor Skill Learning. (7th February 2017) - Thompson, Joseph J.; McColeman, C. M.; Stepanova, Ekaterina R.; Blair, Mark R.
Abstract: Many theories of complex cognitive‐motor skill learning are built on the notion that basic cognitive processes group actions into easy‐to‐perform sequences. The present work examines predictions derived from laboratory‐based studies of motor chunking and motor preparation using data collected from the real‐time strategy video game StarCraft 2. We examined 996, 163 action sequences in the telemetry data of 3, 317 players across seven levels of skill. As predicted, the latency to the first action (thought to be the beginning of a chunked sequence) is delayed relative to the other actions in the group. Other predictions, inspired by the memory drum theory of Henry and Rogers, received only weak support. Abstract : The authors take a new look at an old topic; namely, first action latencies of motor sequences. They examine in‐game actions of 3, 317 players across seven skill levels, and 996, 163 Perception Action Cycles . The differences in skill levels of players reflect vast differences in expertise due, at least in part, to vast differences in the number of hours spent playing StarCraft 2 ™ . The discovery and mystery is that long first action latencies are observed for even the most expert group of players.